Investigations of Structural and Residual Trapping Phenomena during CO2 Sequestration in Deccan Volcanic Province of the Saurashtra Region, Gujarat - Pradeep Reddy Punnam; Balaji Krishnamurthy; Vikranth Kumar Surasani (International Journal of Chemical Engineering)
This work aims to study the structural and residual trapping mechanisms on the Deccan traps topography to elucidate the possible implementation of CO2 geological sequestration. This study provides an insight into a selection of stairsteps landscape from Deccan traps in the Saurashtra region, Gujarat, India. Various parameters affect the efficiency of the structural and residual trapping mechanisms. Thus, the parametric study is conducted on the modeled synthetic geological domain by considering the suitable injection points for varying injection rates and petrophysical properties. The outcomes of this study will provide insights into the dependencies of structural and residual trapping on the Deccan traps surface topography and injection rates. It can also establish a protocol for selecting the optimal injection points with the desired injection rate for the safe and efficient implementation of CO2 sequestration. The simulation results of this study have shown the dependencies of structural and residual trapping on the geological domain parameters.